Parental molecular diversity and its concurrence to heterosis in bread wheat (Triticum aestivum) - KUMAR, VISHNU; MALOO, S R (The Indian Journal of Agricultural Sciences, 2012)
A half diallel set of 10 parents, 45 F1s and 45 F2s was analyzed for grain yield and its components and parental entries were also assessed with RAPD marker for the concurrence of genetic diversity analysis with heterosis and combining ability. Out of 45 crosses, thirteen-thirty one crosses manifested heterotic response for different characters in desired direction. An overall appraisal of GCA effects identified parents DBW 16 and UP 2338 as good general combiners for grain yield and its contributing traits and crosses DBW 16 × UP 2338, DBW 17 × UP 2338 and PBW 373 × Raj 4083, as having high significant positive SCA effects for grain yield as well as for its components. RAPD analysis discemed 352 fragments of which 95 scorable alleles were obtained with 16 primers with an average of 5.93 alleles/primer.